Online Seminar on the Protection of Indonesian Seafarers in the National Shipping Industry - Pratama, Wegig; Wibowo, Waris; Astriawati, Ningrum; Sahudiyono, Sahudiyono (PT Inovasi Pratama Internasional, 2023)
The Indonesian seafaring workforce is one of the inseparable pillars that play a role in this paradigm, having a complexity of its protection, especially those working in the international maritime industry so it becomes a serious concern for the government. The purpose of community service through this online national seminar is to obtain information and recommendations on strengthening the protection of Indonesian seafarer labour in the national shipping industry. The service method through online national seminars is carried out online through the Zoom Meeting application. There were 1187 service participants from various circles, namely government agencies by 20%, private institutions by 25%, academics including university leaders, lecturers by 15%, students/cadets by 35%, general 4% and international 1%. The result of this community service is the strengthening of labour protection of Indonesian seafarers in the international maritime industry accommodating 4 (four) aspects of protection which include: protection on board, protection of travel documents, training education and guard service, and safety and security of life at sea.